Economic and social review for fiscal year - 2009/2010- (Government of Dominica RoseauDM, 2010)
Reviews and analyses Dominica's Growth and Social Protection Strategy (GSPS). Focuses on the macroeconomic performance as well as a review of the implementation of the public sector investment programme, social programmes and the reform agenda.
Documentation Centre has: 2009/10; 2010/11; '2012/13; 2013/14